Actividad antibiótico y antifúngica de B. cepacia provenientes de ambientes nosocomiales. Servicio Autónomo Hospital universitario "Antonio Patricio Alcalá". Cumaná, Venezuela - Araque C Yasmina; Albarado Y Luzmila; Centeno B Sara; Rodríguez-Lemoine Vidal; Vitelli-Flores Juana (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2007)
Abstract: Burkholderia cepacia is a Gram-negative and non-fermenter bacilli, known as a causal agent of opportunistic infections, as well as producer of compounds with antimicrobial activities. In the present study, the antagonism of nine (9) nosocomial isolates of B. cepacia against filamentous fungi, yeast and bacteria from hospital environments was evaluated. The antibacterial and antifungal detection was determined according to the double layer technique and cylindrical sections in agar, respectively. Four B. cepacia isolates (CVCM: 626, 1328, 1331 and 1332) inhibited the different bacterial species analyzed. B. cepacia CVCM 1332 inhibited five (5) of the six (6) indicators of bacterial species, with inhibition halos between 11 and 22 mm, with the exception of P. fluoresecens. Three (3) B. cepacia isolates did not show antibacterial activity. Two B. cepacia isolates inhibited the studied fungi (Fusarium solani, Penicillium citrinum, Penicillium frequentans, Aspergillus niger, Aspergillus ochoraceus, Penicillium echinulatum, Candida tropicalis, Candida famata). The species CVCM 626, 1328 and 1331 showed both antibacterial and antifungal activities. The antagonism of nosocomial B. cepacia isolates against bacteria and fungi from hospital environments was demonstrated, representing an important factor in the colonization of critical areas, facilitating the appearance of infectious symptoms in Resumen: Burkholderia cepacia, es un bacilo Gram negativo, no fermentador, reconocido como causal de infecciones oportunistas; además de producir compuestos con actividad antimicrobiana. En el presente estudio se evaluó el antagonismo de nueve (9) aislados nosocomiales de B. cepacia contra hongos filamentosos, levaduras y bacterias de ambientes hospitalarios. La detección antibacteriana y antifúngica, se determinó según la técnica de la doble capa y de los cortes cilíndricos en agar, respectivamente. Cuatro aislados de B. cepacia (CVCM: 626,1328, 1331 y 1332) inhibieron los diferentes géneros bacterianos analizados. B. cepacia CVCM 1332, inhibió a cinco (5) de las seis (6) especies de bacterias indicadoras, con halos de inhibición entre 11 y 22 mm; a excepción de P. fluorescens. Tres (3) aislados de B. cepacia no presentaron actividad antibacteriana. Dos aislados de B. cepacia inhibieron los hongos estudiados (Fusarium solani, Penicillium citrinum, Penicillium frequentans, Aspergillus niger, Aspergillus ochoraceus, Penicillium echinulatum, Candida tropicalis, Candida famata). Las cepas CVCM 626, 1328 y 1331 presentaron tanto actividad antibacteriana como antifúngica. Se comprobó el antagonismo de aislados nosocomiales de B. cepacia contra bacterias y hongos de ambientes hospitalarios, representando un factor importante en la colonización de áreas críticas, facilitando la aparición de cuadros infecciosos en pacientes allí recluidos.